(untitled) - Pocock, J. G. A. (Cambridge, U.K.,New York, NY, USA, 1999)
In this first volume, The Enlightenments of Edward Gibbon, John Pocock follows Gibbon through his youthful exile in Switzerland and his criticisms of the Encyclopédie and traces the growth of his historical interests down to the conception of the Decline and Fall itself
Keywords: Enlightenment,Thời đại khai sáng; Great Britain,Nước Anh